Circulating saturated fatty acids and risk of gestational diabetes mellitus: A cross-sectional study and meta-analysis - Sun, Zhuo; Deng, Zequn; Wei, Xiaohui; Wang, Na; Yang, Jiaqi; Li, Wenyun; Wu, Min; Liu, Yuwei; He, Gengsheng (Frontiers in Nutrition, 2022)
The aim of this study was to evaluate whether plasma SFAs were in correlation with GDM risks in our in-house women cohort and to better define their associations on the clinical evidence available to date by a dose-response meta-analysis. We carried out a prospective cohort study of 807 pregnant women in 2018-2019 (Shanghai, China). GDM was defined according to the criteria of the International Association of diabetes and pregnancy study groups. Gas chromatography was used to determine the plasma fatty acids (FAs) in the 24-28 gestational weeks. The SFAs levels of non-GDM and GDM participants were compared, and the association between SFAs and GDM was explored by multivariate logistic models. Further, the potential diagnostic value of plasma SFAs was evaluated using receiver operating characteristic (ROC) analysis. For meta-analysis, five databases were systematically searched, and we included 24 relevant studies for calculating pooled standard mean differences (SMD) to describe the differences in SFAs profiles between non-GDM and GDM women. Study-specific, multivariable-adjusted ORs were also pooled. In our cross-sectional study, we found plasma proportion of palmitic acid (C16:0) was positively associated, while plasma stearic acid (C18:0), arachidic acid (C20:0), behenic acid (C22:0), and lignoceric acid were inversely associated with GDM. The area under the receiver operative characteristic curve increased from 0.7503 (the basic diagnostic model) to 0.8178 (p = 0.002) after adding total very-long-chain SFAs (VLcSFAs). A meta-analysis from 25 studies showed the circulating levels of three individual SFAs of GDM women were different from those of normal pregnant women. The summarized ORs for GDM was 1.593 (95% CI: 1.125, 2.255, p = 0.009), 0.652 (95% CI: 0.472, 0.901, p = 0.010) and 0.613 (95% CI: 0.449, 0.838, p = 0.002), respectively, comparing the highest versus lowest quantile of the concentrations of C16:0, C22:0 and C24:0. Our results, combined with the findings from meta-analysis, showed that women with GDM had a particular circulating SFA profile, characterized by higher levels of palmitic acid, and lower levels of VLcSFAs. Alterations in the chain lengths of blood SFA profile were shown to be associated with the occurrence of GDM.